Bird's eye view analysis of in situ cholesterol metabolic pathways in breast cancer patients and its clinicopathological significance in their subtypes. Issue 221 (July 2022) - Kosaka, Shinkichi; Miyashita, Minoru; McNamala, Keely; Nomura, Miyuki; Shima, Hiroshi; Kawai, Masaaki; Sato, Ikuro; Harada-Shoji, Narumi; Ishida, Takanori; Choi, Man Ho; Sasano, Hironobu
Abstract: Obesity has been known to increase the risks of breast cancer (BC) development and also to be associated with adverse clinical outcome of the patients. Abnormalities of cholesterol metabolism are not only related to obesity but also to biological or clinical behavior of BC patients. However, which metabolites or pathways of cholesterol metabolism could represent the characteristics of BC patients have remained virtually unknown. Therefore, in this study, we attempted to perform bird's eye view or comprehensive analysis of in situ or intra-tumoral cholesterol metabolic pathways using the multimodal approaches in order to elucidate the possible significance of cholesterol metabolites and its metabolic enzymes including CYP27A1, CYP7A1, and CYP46A1. GC-MS study using BC specimens was first performed in 60 BCE patients to evaluate cholesterol metabolism from cholesterol through oxysterols in both BC and normal tissues. Results of those analyses above lead to evaluating immunoreactivity and mRNA expression of CYP27A1, CYP7A1 and CYP46A1 in 213 and 153 BCE cases, respectively. Results of comprehensive GC-MS analysis did reveal that three oxysterols, 27-HC, 7α-HC and 24-HC were all related to malignant phenotypes in BC. 27-HC abundance was significantly associated with higher tumor stage ( P  = 0.0475) of BC patients. Luminal B type BC patients harboring high CYP27A1, the enzyme responsible for production of 27-HC were significantly associated with worse disease-free survival than those with low CYP27A1 ( P  = 0.0463). 7α-HC tended to be more abundant in HER2 positive and TNBC subtypes and higher levels of 7α-HC were also significantly associated with higher Ki-67 labeling index ( P  = 0.0022) and histological grade ( P  = 0.0286). CYP7A1, the enzyme involved in production of 7α-HC, was significantly more abundant in TNBC than other subtypes (vs Luminal A; P  = 0.0321, vs Luminal B; P  = 0.0048, vs HER2; P  = 0.0103). The levels of 24-HC in BC were lower than normal breast tissues regardless of its subtypes. CYP46A1, the enzyme involved in the production of 24-HC, was detected only in 33 (15.5%) out of 213 BCE cases examined in this study. Results of our bird's eye view analysis of in situ or intra-tumoral cholesterol metabolism in BC patients did firstly reveal BC subtype dependent involvement of its different pathways. Results also indicated the therapeutic possibility of subtype dependent modification of cholesterol metabolizing pathways in BC patients. Highlights: This is the first study to perform comprehensive analysis of in situ or intra-tumoral cholesterol metabolic pathways. Different breast cancer subtypes have the different cholesterol metabolic pathways to achieve cancer progression. The study indicated the therapeutic possibility of subtype dependent modification of cholesterol metabolizing pathways.